Development and testing of a low-cost portable soil apparent electrical conductivity sensor - Venturin, José Carlos; Alves de Souza, Cristiano Márcio; Prado, Esmael Dias; Bottega, Eduardo Leonel; França da Silva, Leonardo; Soares Arcoverde, Sálvio Napoleão; Paniagua Mendieta, Fernando Mateus; Leyva Rafull, Leidy Zulys; Crespo de Oliveira, Victor [UNESP] (AIP Publishing, 2025)
In modern agriculture, the quest for increased productivity necessitates a comprehensive understanding of crop conditions. A critical component of this is soil analysis, which is essential for developing effective strategies that enhance productivity while minimizing environmental impacts and reducing production costs. The soil apparent electrical conductivity (ECa) sensor is a valuable tool in precision agriculture, offering a cost-effective and time-efficient alternative for soil analysis. This study aimed to develop a portable ECa sensor for diverse applications in agriculture and test it under field conditions aiming for its application as a precision agriculture tool. The development process was divided into four key stages: sensor construction, electronic circuit design, implementation of the embedded control program, and both laboratory and field testing in agricultural settings. The sensor was designed to expedite measurements, with a focus on achieving precision and accuracy in the electronic circuit. Data collected using the ECa meter were analyzed under various conditions, including dry and moist soils, and in a white oat production field. Spatial variability was assessed, leading to the generation of ECa management zone maps. The developed sensor demonstrated ease of operation, rapid measurement capabilities, and performance comparable to commercial meters within the operating range. The findings indicate that the portable ECa meter is a viable tool for analyzing soil spatial variability in precision agriculture systems.